Direct next-generation sequencing of virus-human mixed samples without pretreatment is favorable to recover virus genome. Issue 1 (December 2016) - Li, Dingchen; Li, Zongwei; Zhou, Zhe; Li, Zhen; Qu, Xinyan; Xu, Peisong; Zhou, Pingkun; Bo, Xiaochen; Ni, Ming
Abstract Next-generation sequencing (NGS) enables the recovery of pathogen genomes from clinical samples without the need for culturing. Depletion of host/microbiota components (e.g., ribosomal RNA and poly-A RNA) and whole DNA/cDNA amplification are routine methods to improve recovery results. Using mixtures of human and influenza A virus (H1N1) RNA as a model, we found that background depletion and whole transcriptome amplification introduced biased distributions of read coverage over the H1N1 genome, thereby hampering genome assembly. Influenza serotyping was also affected by pretreatments. We propose that direct sequencing of noncultured samples without pretreatment is a favorable option for pathogen genome recovery applications. Reviewer This article was reviewed by Sebastian Maurer-Stroh.